Follow up of meningomyelocele and associated hydrocephalus, bladder and/or bowel incontinence and foot deformity in a developing country - Dikshit, Vishesh; Gupta, Abhaya; Patil, Prashant; Kekre, Geeta; Kothari, Paras; Kulkarni, Apoorva (International Surgery Journal, 2017)
Background: Meningomyelocele (MMC) and meningocele (MC) are the two most common types of neural tube defects (NTD) seen. Some of the problems associated with care of these patients are psychological stress is parents, average financial condition of caretakers, ignorance on the part of parents, local physicians for management of this condition, very few dedicated Spina bifida clinics and social stigma associated with this condition. The aim of treatment of meningomyelocele is to the patients with maximum mobility and social continence which is possible through multidisciplinary care involving paediatric surgeon, paediatrician, nursing staff, occupational therapist, physiotherapist, social worker, parents and patients themselves. The aim of this study is to discuss our experience in initial management of meningomyelocele (MMC) and hydrocephalus and long-term management of bladder/bowel incontinence and foot deformity in a tertiary care hospital of a developing country. Methods: A retrospective nonrandomized observational study was conducted in the department of pediatric surgery at a tertiary hospital, from August 2008 to October 2015. Overall 145 patients of meningomyelocele were included in the study. Patients were managed according to our institution protocol. Results: 68.2% MMC patients were repaired primarily. 24.1% of total patients needed Y-V plasty skin advancement flap. 7.5% patients needed synthetic patch for dural closure. 24.1% patients were incontinent since birth. 19.3% patients had decreased lower limb power since birth. 5.5% patients were incontinent after MMC repair. 8.2% patients had decreased lower limb power after MMC repair. 28.9% patients needed VP shunt for gross hydrocephalus before MMC repair. 51.03% patients needed VP shunt after MMC repair. 20% patients did not require VP shunt in the present series. 13.1% patients in the present series had urinary incontinence. 11.03% patients had fecal incontinence. 73.6% patients with urinary incontinence were successfully managed with conservative treatment. 87.5% patients with fecal incontinence responded to conservative treatment. Bladder augmentation was done in 26.3% of neurogenic bladder dysfunction patients. 60% of these patients had dry interval of more than 4 hours. MACE was done in 12.5% of neurogenic bowel dysfunction patients. 2 patients required simultaneous bladder augmentation, Mitrofanoff’s and MACE procedure. One of these patients achieved a dry interval of >4 hour. Conclusions: Successful rehabilitation of children with MMC can be achieved with parental education and support, dedicated clinicians, trained nursing staff, regular follow-up and low threshold for diagnosing clinical deterioration and proactive management to prevent further clinical deterioration.